2014
DOI: 10.1002/14651858.cd000238.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory oxygen for people with chronic obstructive pulmonary disease who are not hypoxaemic at rest

Abstract: Cochrane Database of Systematic Reviews Ambulatory oxygen for people with chronic obstructive pulmonary disease who are not hypoxaemic at rest (Review) Ameer F, Carson KV, Usmani ZA, Smith BJ Ameer F, Carson KV, Usmani ZA, Smith BJ. Ambulatory oxygen for people with chronic obstructive pulmonary disease who are not hypoxaemic at rest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 21 publications
0
18
1
3
Order By: Relevance
“…5,6,24 Our findings contrast with the prolonged survival that was observed among patients with COPD and severe desaturation who were treated with supplemental oxygen. 1,2 Possible reasons for this discrepancy are the nonlinear threshold effects of oxygen saturation on pulmonary vasoconstriction, mediator release, and ventilatory drive, 25,26 which occur with an SpO 2 of 88% or less and which may be more important in patients with chronic hypoxemia.…”
Section: Discussioncontrasting
confidence: 90%
“…5,6,24 Our findings contrast with the prolonged survival that was observed among patients with COPD and severe desaturation who were treated with supplemental oxygen. 1,2 Possible reasons for this discrepancy are the nonlinear threshold effects of oxygen saturation on pulmonary vasoconstriction, mediator release, and ventilatory drive, 25,26 which occur with an SpO 2 of 88% or less and which may be more important in patients with chronic hypoxemia.…”
Section: Discussioncontrasting
confidence: 90%
“…A systematic review of four randomised placebo-controlled trials of AOT in patients with COPD concluded that oxygen improved exertional dyspnoea, without survival benefit or enhanced exercise capacity [64]. The review included patients without significant resting hypoxaemia, defined as meeting the criteria for LTOT, with the duration of intervention varying between 2 and 12 weeks.…”
Section: Ambulatory Oxygen Therapy In Copd and Ildmentioning
confidence: 99%
“…Die Laboratorien müssen grundsätzlich geeignet sein, die geforderten Ausbildungsinhalte zu vermitteln. sein, welcher bei diesen Patienten häufig zu finden ist [20,28], und der die Zwerchfellermüdung während Atemmuskelbelastung verstärken kann [32].…”
Section: Laboratorien Für Die Ausbildung Auf Dem Gebiet Der Klinischeunclassified